Regions Matter: How Localized Social Capital Affects Innovation and External Knowledge Acquisition - Laursen, Keld; Masciarelli, Francesca; Prencipe, Andrea (Organization Science, 2012)
To introduce new products, firms often use knowledge from other organizations. Drawing on social capital theory and the relational view of the firm, we argue that geographically localized social capital affects a firm's ability to innovate through various external channels. Combining data on social capital at the regional level, with a large-scale data set of the innovative activities of a representative sample of 2,413 Italian manufacturing firms from 21 regions, and controlling for a large set of firm and regional characteristics, we find that being located in a region characterized by a high level of social capital leads to a higher propensity to innovate. We find also that being located in an area characterized by a high degree of localized social capital is complementary to firms' investments in internal research and development (R&D) and that such a location positively moderates the effectiveness of externally acquired R&D on the propensity to innovate.